If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(-7x + 1) = -55 Reorder the terms: 1(1 + -7x) = -55 (1 * 1 + -7x * 1) = -55 (1 + -7x) = -55 Solving 1 + -7x = -55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -7x = -55 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = -55 + -1 -7x = -55 + -1 Combine like terms: -55 + -1 = -56 -7x = -56 Divide each side by '-7'. x = 8 Simplifying x = 8
| 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 | | 7(7r+19)=7-14r | | 12x+3=-10 | | -8x+4x+6x=-6 | | -12x+2y=-14 | | 3(7h-15)=9+18h | | -7(7-3x)=-175 | | 16x+8=-3 | | q/8-5=9 | | -17w+7(17w+12)=18w | | 5x+2-6x=-11 | | 702/u=27 | | 18.94+15.8g=-3(-18.8g+11.28) |